Attitudes and knowledge about medical cannabis among Israeli and American nursing students. (April 2021) - Zolotov, Yuval; Grinstein Cohen, Orli; Findley, Patricia A.; Reznik, Alexander; Isralowitz, Richard; Willard, Suzanne
Abstract: Background: Although medical cannabis regulations are emerging in many places around the world, a contentious conundrum remains within the medical establishment regarding the appropriate part that cannabis may have in the provision of health care. Nurses have an indispensable role in the care management of patients, and given the consideration of cannabis as a possible treatment, they are warranted to be aware of its medical properties, as well as to be able to adequately answer patient queries. Nevertheless, very little is currently known about nurses' perceptions related to medical cannabis. Objective: To assess attitudes, beliefs and knowledge about medical cannabis among nursing students. Methods: Cross-sectional study in two universities: Rutgers University (RU) in New Jersey and Ben Gurion University of the Negev (BGU) in Israel. In addition to demographic data, the survey instrument included questions about attitudes, beliefs, knowledge, and training. Results: Overall, 387 students participated, mainly females (87.8%). The vast majority from both sub-groups stated they would recommend cannabis to their patients if allowed to do so (91.2%), and were in agreement that medical cannabis is associated with significant benefits for physical (93.5%) and mental (87.8%) health. Compared to the BGU sub-group, more students from RU stated that they feel prepared to answer patient questions about medical cannabis (19.5% vs. 33.5%, respectively; χ 2 = 9.74, p < 0.01). While the majority of respondents stated they have not received any formal education related to medical cannabis, they expressed endorsement for such training and education. Conclusions: In light of the expanding number of patients who use medical cannabis, this study highlights the importance of incorporating medical cannabis education for nurses in academic and clinical curricula.